2022
DOI: 10.1093/sleep/zsac031
|View full text |Cite
|
Sign up to set email alerts
|

Combining cardiac monitoring with actigraphy aids nocturnal arousal detection during ambulatory sleep assessment in insomnia

Abstract: Study Objectives The objective assessment of insomnia has remained difficult. Multisensory devices collecting heart rate (HR) and motion are regarded as the future of ambulatory sleep monitoring. Unfortunately, reports on altered average HR or heart rate variability (HRV) during sleep in insomnia are equivocal. Here, we evaluated whether the objective quantification of insomnia improves by assessing state-related changes in cardiac measures. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Lack of consistent daily routines has been reported to predict increased bedtime resistance for children with ADHD [ 40 ], and interventions for better sleep hygiene and parenting consistency decreased bedtime resistance [ 41 ]. These findings may be consistent with our current report that children’s bedtime resistance, night waking, parasomnias and sleep anxiety are significantly correlated with parental insomnia probability, as insomnia disorder is associated with greater sleep timing variability and less consistent sleep routines [ 42 ]. As such, greater parental insomnia symptoms may result in less-consistent household bedtime routines which in turn would contribute to children’s bedtime resistance, sleep anxiety and night-time wakenings.…”
Section: Discussionsupporting
confidence: 93%
“…Lack of consistent daily routines has been reported to predict increased bedtime resistance for children with ADHD [ 40 ], and interventions for better sleep hygiene and parenting consistency decreased bedtime resistance [ 41 ]. These findings may be consistent with our current report that children’s bedtime resistance, night waking, parasomnias and sleep anxiety are significantly correlated with parental insomnia probability, as insomnia disorder is associated with greater sleep timing variability and less consistent sleep routines [ 42 ]. As such, greater parental insomnia symptoms may result in less-consistent household bedtime routines which in turn would contribute to children’s bedtime resistance, sleep anxiety and night-time wakenings.…”
Section: Discussionsupporting
confidence: 93%
“… 59 One study used actigraphy to obtain HRV features in patients with insomnia and reported significant differences in HR, the SDNN, and the RMSSD between those patients’ awake and asleep states. 60 …”
Section: Discussionmentioning
confidence: 99%
“…It is not unlikely that a much larger number of null results have been left unreported (Rosenthal, 1979 ). In recent years, vast efforts have been undertaken to improve the quality of actigraphy sleep estimates for insomnia research (Angelova et al, 2020 ; Rösler et al, 2022 ; te Lindert et al, 2020 ). In a retrospective study of more than 400 participants, Natale et al ( 2014 ) concluded that actigraphy satisfactorily differentiates patients with insomnia from controls, when the correct quantitative actigraphic criteria for the used device are applied.…”
Section: Discussionmentioning
confidence: 99%